A melancolia de resistência como identidade: um estudo sobre as obras Mayombe e A Geração da Utopia de Pepetela - Silva, Cibele Verrangia Correa da (2018)
This thesis analyzes two pieces of modern Angolan literature: Mayombe (1980) and A Geração da Utopia (1992), by Angolan writer Pepetela. We seek to develop an analytical and comparative study between the aesthetic and structural elements of both works, focusing on the narrator and main characters figures in order to problematize the political engagement present on Angolan literature from the decolonization period. We bring the hypothesis that a specific melancholic discourse highlights the identities that suppose resistance to the colonial yoke and to the new nationalist commands. This proposed study reason can be searched specially on the fact that the engagement and melancholy of the author is, also, of people who constitute its identities in a post-colonial context, in the tensions of cultural hybridity, displacements, transits, divisions and fissures of modern project, which brings out a variety of struggles around, among others, blackness, pan-Africanism, tribalism, Angolanity, gender relations, traditions and their translations, neoliberal advancement, disenchantment, melancholy and resistance.